DETERMINATION OF PLASTIC DEFORMATION COEFFICIENT FOR ONE-EDGE DRILLS - Tanya AVRAMOVA; Evstati LEFTEROV (Fiabilitate şi Durabilitate)
The plastic deformation coefficient, also called the relative plastic deformation, is related to the angle of shifting of the chip and the rake angle of the tool. Studying the nature of chip shifting and deforming layer material relative to the face and major flank of the tool is of great importance for determining both the workability of the materials and the correct choice of cutting tool characteristics. This article proposes a methodology based on mathematical dependencies for determining the coefficient of plastic deformation. Theoretical results are presented based on the proposed methodology, as well as results of experimental studies.